GENERAL DESCRIPTION OF CORRUPT BEHAVIOR - Karimova Muyassarkhon Abdukayumovna; Gofforov Zafariddin Zaynobiddinovich (Galaxy International Interdisciplinary Research Journal, 2023)
Corruption it's a terrible vile vile that can spark society in different ways. In this article ,it is thought that this will undermine the foundations of democracy and the rule of law, lead to violations of human rights, create conditions for the deterioration of the quality of life.In particular, the general characteristics of the behavior of a corrupt person are analyzed scientifically – philosophically, psychologically.